Control of cellular adhesion and myofibroblastic character with sub-micrometer magnetoelastic vibrations. (11th April 2018) - Holmes, Hal R.; Vlaisavljevich, Eli; Tan, Ee Lim; Snyder, Katherine L.; Ong, Keat Ghee; Rajachar, Rupak M.
Abstract: The effect of sub-cellular mechanical loads on the behavior of fibroblasts was investigated using magnetoelastic (ME) materials, a type of material that produces mechanical vibrations when exposed to an external magnetic AC field. The integration of this functionality into implant surfaces could mitigate excessive fibrotic responses to many biomedical devices. By changing the profiles of the AC magnetic field, the amplitude, duration, and period of the applied vibrations was altered to understand the effect of each parameter on cell behavior. Results indicate fibroblast adhesion depends on the magnitude and total number of applied vibrations, and reductions in proliferative activity, cell spreading, and the expression of myofibroblastic markers occur in response to the vibrations induced by the ME materials. These findings suggest that the subcellular amplitude mechanical loads produced by ME materials could potentially remotely modulate myofibroblastic activity and limit undesirable fibrotic development.